Epidemiology of back pain in the teaching districts of B. P. Koirala Institute of Health Sciences (Health Renaissance, 2011)
Introduction: The prevalence of back pain is very high in the general population but little is known about the predictors of back pain in the general population. Though certain risk factors have been associated with back pain, these are mentioned in Western literature. It is not known how much of these hold true for a developing country like Nepal. Objective: To estimate the prevalence of back pain in the Teaching Districts of B.P.Koirala Institute of Health Sciences and to identify predictors of back pain in the community. Materials and Methods: Three hundred and fourteen persons of eighteen years and above were included in this cross-sectional descriptive study conducted from January 2006 to December 2009 using pretested questionnaires. Results: The annual prevalence of back pain among males (67.9%) and females (74.3%) were similar (P>0.05) and the overall annual prevalence was 71%. The highest prevalence of back pain was found in the age group of 31-40 years. Age, marriage and occupation were related significantly to the occurrence of back pain. The total duration of back pain in one year was less than 15 days in 73%. The number of workdays lost was upto 5 in 81% of people with back pain. Conclusion: Back pain is a very common complaint among the adult population in the community. Population belonging to 31-50 age group, married status and farmers and labourers are more prone to have back pain. Gender, height and weight are not associated with back pain. Keywords: back pain; predictors; community. DOI: http://dx.doi.org/10.3126/hren.v9i3.5582   HR 2011; 9(3): 152-156